UNDERSTANDING OF KEY BUILDING PERFORMANCE CRITERIA FOR CONTEMPORARY MOSQUE FACILITIES - Rohimah Khoiriyah Harahap; Maimunah Sapri; Ibrahim Atan @ Sipan (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
Mosque facilities that fail to perform either physically, environmentally, or functionally can cause harm, discomfort, and dissatisfaction to users and eventually demotivate the community to the mosque. This scenario demonstrates the need to improve mosque facilities to meet the contemporary needs of the community. The purpose of this study is to document key building performance criteria for contemporary mosque facilities which will be used to guide the development of its classification in a future study. Literature review search through Web Of Science from 1997 to 2020 was conducted using the terms "mosque building performance criteria", "mosque facility performance criteria", "building performance criteria", and "facility performance criteria". By applying the "Literature Review Synthesis Process", the authors conducted cross-analysis, synthesis, and categorization into meaningful themes that represent building performance criteria for mosque facilities. The result of the review highlighted three (3) building performance criteria for contemporary mosque facilities; physical, environmental, and functional. Results are expected to develop a future framework of building performance criteria for mosque facilities that supports the fundamental functions of mosque for the contemporary community needs. It will significantly guide architects and facilities managers to develop community-centric facilities guidelines in the field of architecture and facilities management.